2017
DOI: 10.3892/mmr.2017.6239
|View full text |Cite
|
Sign up to set email alerts
|

Serum microRNA profiling and bioinformatics analysis of patients with type 2 diabetes mellitus in a Chinese population

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by islet β-cell dysfunction and insulin resistance, which leads to an inability to maintain blood glucose homeostasis. Circulating microRNAs (miRNAs) have been suggested as novel biomarkers for T2DM prediction or disease progression. However, miRNAs and their roles in the pathogenesis of T2DM remain to be fully elucidated. In the present study, the serum miRNA expression profiles of T2DM patients in Chinese cohorts were examined. Total RNA was extracted from ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 80 publications
0
26
0
Order By: Relevance
“…Aberrant miR-766-3p expressions in renal cell carcinoma and HCC have been reported [13,14]. MiR-766-3p reveals as an inhibitor or inducer of tumor progression in various cancer types and it has recently received much attention since its significant role in human cancer [15,16]. However, it's interesting to note that miR-766-3p expression is reduced in HCC compared with noncancerous liver tissues, demonstrating that miR-766-3p may be a potential tumor suppressor in HCC [15].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant miR-766-3p expressions in renal cell carcinoma and HCC have been reported [13,14]. MiR-766-3p reveals as an inhibitor or inducer of tumor progression in various cancer types and it has recently received much attention since its significant role in human cancer [15,16]. However, it's interesting to note that miR-766-3p expression is reduced in HCC compared with noncancerous liver tissues, demonstrating that miR-766-3p may be a potential tumor suppressor in HCC [15].…”
Section: Discussionmentioning
confidence: 99%
“…N = 6-8 retinas/group. streptozotocin-induced diabetes rats (Wu et al, 2012) and in the plasma of type-2 diabetic patients (Yang et al, 2017), while miR-96 is downregulated in the RHO-mouse retina, a model for common form of inherited blindness (Palfi et al, 2016). In addition, hypoxic conditions in cancer cells have shown to modify the expression profiling of miRNAs (Shen et al, 2013;Bandara et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…IRS-1 levels also showed a negative correlation with increased miR-144 expression in the whole blood of T2D subjects, exhibiting a correlation with progressively increased glycemic status [ 127 ]. In another study, miR-96-5p, which also targets IRS-1, was found overexpressed in the serum of T2D subjects, along with miR-144-3p, miR-454-3p, and miR-455-5p, while miR-409-3p, miR-665, and miR-766-3p were reduced [ 128 ]. IRS-1 is also negatively regulated by miR-126, which was found to be overexpressed by hepatocytes in an in vitro model of insulin resistance [ 129 ].…”
Section: Mirnas and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…MiR-144 is overexpressed in T2D and regulates the IRS, the initiator of insulin signaling [ 127 , 128 ]. This is one of the molecular mechanisms leading to insulin resistance.…”
Section: Exercise and Cardiovascular Protectionmentioning
confidence: 99%